2016
DOI: 10.1038/srep26005
|View full text |Cite
|
Sign up to set email alerts
|

Stigmergy co-ordinates multicellular collective behaviours during Myxococcus xanthus surface migration

Abstract: Surface translocation by the soil bacterium Myxococcus xanthus is a complex multicellular phenomenon that entails two motility systems. However, the mechanisms by which the activities of individual cells are coordinated to manifest this collective behaviour are currently unclear. Here we have developed a novel assay that enables detailed microscopic examination of M. xanthus motility at the interstitial interface between solidified nutrient medium and a glass coverslip. Under these conditions, M. xanthus motil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Moreover, gliding cells deposit a slime trail. The function and composition of slime are unknown; however, slime may promote the adhesion of cells to the substratum and may contain polysaccharides and OM vesicles (Ducret et al , ; ; Gloag et al , ). We conclude that LPS is (conditionally) important for both motility systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, gliding cells deposit a slime trail. The function and composition of slime are unknown; however, slime may promote the adhesion of cells to the substratum and may contain polysaccharides and OM vesicles (Ducret et al , ; ; Gloag et al , ). We conclude that LPS is (conditionally) important for both motility systems.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, transfer of lipoproteins may also have negative effects on recipients, as is the case for the transfer of toxins that kill non-immune recipient cells (Vassallo et al, 2017). Other toxins that kill non-immune cells are transferred in a contact-dependent manner by the type VI secretion system (Gong et al, 2018;Troselj et al, 2018). Finally, during the starvation-induced formation of spore-filled fruiting bodies, transmission of the cell-cell contact-dependent C-signal is essential for the completion of this developmental program (Kim and Kaiser, 1990a;1990b).…”
Section: Introductionmentioning
confidence: 99%
“…Exopolysaccharides, the major fraction of ECM, form polymeric networks that provide essential structural support and surface adhesion for biofilms (Berk et al ., ). ECM of the soil bacterium Myxococcus xanthus contains EPS (∼55%), proteins (∼45%) and a small amount of lipids and extracellular DNA (Curtis et al ., ; Behmlander and Dworkin, ; Hu et al ., ; Gloag et al ., ). M. xanthus EPS is composed of various monosaccharides including glucose, rhamnose, mannose and N ‐acetyl glucosamine (Behmlander and Dworkin, ; Gibiansky et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Third, pili assembly and EPS production are mutually regulated (Yang et al ., ; Li et al ., ). Fourth, M. xanthus cells, like P. aeruginosa , also show trail‐following behaviors (Gibiansky et al ., ; Gloag et al ., ). Fifth, in a recent report, Berleman et al found that EPS forms honeycomb‐like microchannels that facilitate S‐motility and biofilm formation by aligning individual cells (Berleman et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, several bacterial species modify their local environment and cooperative behaviors to promote swarm colony expansion. For example, surface-motile cells appear to migrate along shared tracks comprised of furrows in the medium lined with extracellular material in Pseudomonas aeruginosa and M. xanthus (41)(42)(43). In P. mirabilis, swarm colonies can produce extracellular slime trails that appear to spatially coordinate swarming cells to promote swarm colony expansion (44).…”
Section: Discussionmentioning
confidence: 99%